Natural resource and economic growth nexus in Nigeria: a disaggregated approach - Inuwa, Nasiru; Adamu, Sagir; Sani, Mohammed Bello; Modibbo, Haruna Usman (Letters in spatial and resource sciences, 2022)
This study examined the disaggregated effect of natural resource rents on economic growth in Nigeria during the period 1981–2017. The study applied both traditional and modern unit root tests that accounts for structural breaks to examine the properties of the variables. The study also applied Bayer and Hanck combined cointegration test, canonical cointegration regression (CCR) and fully modified OLS (FMOLS). The results revealed the presence of long run equilibrium relationship among the variables. The results from the long run analysis revealed that oil and forest rents negatively affect economic growth in Nigeria, thereby suggesting resource curse hypothesis. However, natural gas, coal and mineral rents positively affect economic growth. Similarly, the study revealed that financial development stimulates economic growth. The policy implication of the findings is that different types of resource rents have different impact on economic growth as evidenced in this study. Therefore, the study suggests that government should use the rents judiciously in order to stimulate growth. This can be achieved through reinvesting in other growth enhancing sectors of the economy such as financial sector as evidenced in the study. Also, policy makers should design and implement policies that will sustain the good use of the rents obtained from the other resources (coal, mineral and natural gas) so that it will continue to serve as blessing rather than a curse on the Nigerian economy.